Analysis of Cricket Ball Type and Innings on State Level Cricket Batter’s Performance - Connor, Jonathan Douglas; Sinclair, Wade H.; Leicht, Anthony S.; Doma, Kenji (Frontiers in Psychology, 2019)
Background: The aim of this investigation was to compare the type of cricket balls utilized and innings on cricket batting performance in the First-Class Australian competition. Methods: Batting performance measures of 43 state level cricket batters were collected from two seasons of the Sheffield shield tournament (N = 60 games) that incorporated both Kookaburra™ (n = 30 games) and Duke™ (n = 30 games) cricket balls. Results: First-innings batting performances were significantly greater for the average number of runs scored (37.5 ± 13.4 vs. 31.2 ± 11.3), balls faced (60.7 ± 26.2 vs. 49.9 ± 23.6), boundary 4s (3.8 ± 1.9 vs. 2.9 ± 1.4) and boundary 6s (0.2 ± 0.3 vs. 0.1 ± 0.3) scored per game (p < 0.05), as well as centuries scored (5.74 ± 8.56% vs. 1.49 ± 5.14%) compared to second innings performances (p < 0.05). There were no differences for any batting performance measures as a result of ball type (p > 0.05). However, significantly more wickets were taken by pace bowlers during Duke™ ball games (85.0 ± 12.8% vs.76.4 ± 13.9%), while relatively more wickets were taken by spin bowlers during Kookaburra™ ball games (14.2 ± 12.5% vs. 22.0 ± 14.1%; p < 0.05). Conclusions: Cricket batting performance was comparable in games involving the Kookaburra ™ or Duke™ ball. However, pace bowlers were more successful transferring their skill to the Duke™ ball, while spin bowlers were more successful with the KB™ ball. Subsequently, batters may be able to effectively adapt their movement technique, and transfer their skill to the Duke™ ball conditions. Future research is suggested to examine the influence of the cricket playing surface’s deterioration on cricket batter’s interceptive performance.